Revealing the Production Mechanism of High-energy Neutrinos from NGC 1068 - Abhishek Das; B. Theodore Zhang; Kohta Murase (The Astrophysical Journal, 2024)
The detection of high-energy neutrino signals from the nearby Seyfert galaxy NGC 1068 provides us with an opportunity to study nonthermal processes near the center of supermassive black holes. Using the IceCube and latest Fermi-LAT data, we present general multimessenger constraints on the energetics of cosmic rays and the size of neutrino emission regions. In the photohadronic scenario, the required cosmic-ray luminosity should be larger than ∼1%−10% of the Eddington luminosity and the emission radius should be ≲15 R _S in low- β plasma and ≲3 R _S in high- β plasma. The leptonic scenario overshoots the NuSTAR or Fermi-LAT data for any emission radii we consider, and the required gamma-ray luminosity is much larger than the Eddington luminosity. The beta-decay scenario also violates not only the energetics requirement but also gamma-ray constraints, especially when the Bethe–Heitler and photomeson production processes are consistently considered. Our results rule out the leptonic and beta-decay scenarios in a nearly model-independent manner and support hadronic mechanisms in magnetically powered coronae if NGC 1068 is a source of high-energy neutrinos.